2011
DOI: 10.1038/gene.2011.46
|View full text |Cite
|
Sign up to set email alerts
|

Influence of variations across the MMP-1 and -3 genes on the serum levels of MMP-1 and -3 and disease activity in rheumatoid arthritis

Abstract: Matrix metalloproteinases (MMPs) are involved in joint destruction in rheumatoid arthritis (RA), and are strongly associated with levels of inflammation. To understand the relationship between MMP-1 and -3 variants and MMP levels in RA, we investigated the genotypic and haplotypic relationships of the MMP-1 and -3 genes with circulating levels of these MMPs. The genotypes of single-nucleotide polymorphisms (SNPs) rs1799750 (1G/2G, MMP-1 promoter), rs495366 (G/A, intergene), rs679620 (A/G, MMP-3 coding region) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 45 publications
1
31
0
Order By: Relevance
“…A promoter polymorphism within the MMP3 gene (rs3025058) is also believed to be tightly linked to the rs679620 variant (Beyzade et al 2003;Chen et al 2012;Raleigh et al 2009). Both markers are associated with MMP3 expression levels, notably the rs3025058 5A allele and the rs679620 'A' allele are associated with relatively lower levels of MMP3, and the highest level of pathological activity related to rheumatoid arthritis.…”
Section: Discussionmentioning
confidence: 98%
“…A promoter polymorphism within the MMP3 gene (rs3025058) is also believed to be tightly linked to the rs679620 variant (Beyzade et al 2003;Chen et al 2012;Raleigh et al 2009). Both markers are associated with MMP3 expression levels, notably the rs3025058 5A allele and the rs679620 'A' allele are associated with relatively lower levels of MMP3, and the highest level of pathological activity related to rheumatoid arthritis.…”
Section: Discussionmentioning
confidence: 98%
“…MMP-3, also known as a stromelysin-1, has a broader substrate specificity, with activity against type II, III, IV, IX, X and XI collagens, proteoglycans, fibronectin and laminin and is the most widely studied members in RA [15]. MMP-13, which preferentially degrades type II collagen and aggrecan was exclusively expressed in 80-90% patients of RA [36].…”
Section: Discussionmentioning
confidence: 99%
“…The synovial tissue destruction observed in RA is due to the activation MMPs mainly secreted by FLSs, macrophages and chondrocytes [15]. Increased levels of MMPs in the synovial fluid of patients with RA are capable of virtually degrading all structural proteins present at the joints [16].…”
Section: Introductionmentioning
confidence: 99%
“…[32][33][34][35] Cheng et al, 36 in a recent GWA study, found an association between SNP rs650108 located in intron 8 of MMP3 with levels of MMP1. Although these two SNPs (rs645419 and rs650108) were not individually associated with adiposity indices in our study, their combination in haplotype 3 with rs646910 provided a stronger association than either SNP alone, suggesting that this haplotype could tag an additional unmeasured functional polymorphism better than either single SNP alone.…”
Section: Mmp3 and Adiposity Indices In European Children D Cugino Et Almentioning
confidence: 99%